Analisis Peran Reproduksi dan Sosialisasi Perempuan Berprofesi Kupu-Kupu Malam dalam Membentuk Karakter Anak - Fike Windi Nufria Wati; Kunti Dewi Masyithoh; Inayah Inayah; Riski Dwi Agustina; Emmanuella Hernanto Widodo; Didi Pramono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze how the reproductive and socialization roles of women who work as night butterflies influence the formation of children's character. The research method used is a qualitative approach with a case study approach. Data was collected through in-depth interviews and participant observation of five women who work as night butterflies and their five children aged between 5 until 10 years old. The results of the research show that the reproductive role of women who work as night butterflies tend to be less involved in the development of their children. They often focus more on their work and have less time to accompany their children. Meanwhile, socialization carried out by women who work as night butterflies tends to have a negative influence on children's character. Children of night butterfly women often experience emotional instability and lack of adequate attention from their parents. Thus, the reproductive and socialization roles of women who work as night butterflies can have a negative impact on the formation of children's character. Therefore, greater efforts are needed from the government and society to provide support and protection to women in the night butterfly profession so that they can provide adequate attention to their children and help in forming their character.